POLA PEMANFAATAN WAKTU LUANG MAHASISWA SOSIOLOGI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Muhammad Syukri Hanafi; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRCT This research are used for known the pattern of utilization of leisure time by sociology students at the Faculty of Social and Political, Riau University. The responses given by students (respondents) of course different. This difference can be seen from the use of free time, there is self-development, relaxation, or recreation. This research has 551 populations. This research used the slovin formula to determine the sample and obtained 186 samples. The sampling technique in this research are proportional random sampling. The Final Data was carried out through primary data using questionnaires and secondary data. From the results of this research, we can see that most students use their free time to do relaxation activities, such as resting, venting or worshiping. Key words: Student Leisure Time, Self-Development, Relaxation, Recreation